Survey of Gastrointestinal Parasitic Infection in Captive Lions in Egypt - Mohammed, Alaa H.; Farag, Heba S.; Khalifa, Marwa M.; Yehia, Shimaa G.; Rakha, Gamal M. (Journal of Advanced Veterinary Research, 2024)
A coprological survey was conducted to determine the types and prevalence of internal parasites in captive African lions (Panthera leo) in Egypt. Individual fecal samples were collected from 30 lions of different ages and gender from Giza Zoo and different circuses over a 1-year period. Young, aged lions were suffered from weight loss, lethargy, and mild decrease in appetite with mild gastrointestinal symptoms and vomiting with presence of adult toxascaris leonina in vomitus of 3 of them while adult ones show normal body condition without any symptoms. Fecal samples were subjected for macroscopic examination then examined using flotation and sedimentation techniques to assess the presence of parasite eggs and oocysts. The overall prevalence of helminth infections was 33.33% (10/30). Eggs of Toxascaris leonina were found in the feces of 6 (6/10, 60%) lions and Taenia species in 4 (4/10, 40%) lions. In conclusion, due to the increased number of lions in Egypt either for the purpose of acquisition or for work in show as in circus and in the zoo, therefore, diseases that affect lions must be taken into consideration. Parasitic disease is of veterinary importance for lions, but future work including other parasitic, bacterial and viral infections, epidemiology, disease distribution, line of prevention and control for each problem are required.